2019
DOI: 10.1037/xhp0000687
|View full text |Cite
|
Sign up to set email alerts
|

Self-associated stimuli produce stronger intentional binding.

Abstract: Self-generated actions are important for survival; they influence perception, especially the subjective time between the action and its outcome, known as intentional binding (IB). Whereas most studies on IB have examined the role of action being associated with the self or not, the role of the outcome being associated with the self or not has received less attention. The major models or mechanisms proposed to explain IB do not explicitly discuss the role of self-association without confounding it with intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 37 publications
0
19
2
2
Order By: Relevance
“…In addition to the PQ-16 questionnaire exploring attenuated psychosis, the self-preference task was added to provide an objective self-related measure. It has repeatedly been shown that a stimulus we associate with ourselves is processed faster and with higher accuracy than a stimulus we associate with others 104,105 . These effects can be accounted for either by a self-referent memory advantage 106 or by enhanced attention drawn to self-related information 107 .…”
Section: Resourcementioning
confidence: 99%
“…In addition to the PQ-16 questionnaire exploring attenuated psychosis, the self-preference task was added to provide an objective self-related measure. It has repeatedly been shown that a stimulus we associate with ourselves is processed faster and with higher accuracy than a stimulus we associate with others 104,105 . These effects can be accounted for either by a self-referent memory advantage 106 or by enhanced attention drawn to self-related information 107 .…”
Section: Resourcementioning
confidence: 99%
“…3; Sui & Humphreys, 2015d), tâche local/global dite de Navon (Liu & Sui, 2016; Sui, Liu, et al, 2015), tâche anti-saccade mesurant la capture attentionnelle (Yankouskaya et al, 2016), tâche de mouvements oculaires (Dalmaso et al, 2019), tâche de recherche visuelle oculomotrice évaluant la sélection visuelle (Siebold et al, 2015; Wade & Vickery, 2018), tâche mesurant l’accès du stimulus à la conscience visuelle ( breaking continuous flash suppression , Macrae et al, 2017; Stein et al, 2016), tâche évaluant la sensibilité au contraste visuel de cibles suite à la présentation d’indices périphériques (formes géométriques préalablement associées à soi, ami, étranger, Macrae et al, 2018, Exp. 1), tâche évaluant la mémoire de travail (Yin et al, 2019) ou tâche d’évaluation de durée (Constable, Welsh, et al 2019; Makwana & Srinivasan, 2019).…”
Section: L’effet De Priorité Au Soi (Eps)unclassified
“…De plus, de par la simplicité et la robustesse de la tâche d’appariement qui le mesure, il pourrait permettre d’approcher de manière expérimentale et aussi objective que possible un construit par définition subjectif, le Soi, et ses différentes propriétés ou les phénomènes qui y sont rattachés, notamment à l’œuvre dans la cognition sociale. Parmi eux, de récents travaux témoignent de la créativité stimulée par l’emploi de cette tâche, qui a permis d’examiner les mécanismes à l’œuvre dans le phénomène d’intégration intentionnelle ( intentional binding , i.e., le fait que la durée subjective entre une action et son résultat perçu soit plus courte lorsque cette action est auto-initiée vs hétéro-initiée, Makwana & Srinivasan, 2019), la perception de la localisation corporelle du Soi (Schäfer et al, 2019) ou les biais égocentriques et hétérocentriques, dont l’EFS serait un candidat prédicteur au moins aussi important que la distinction soi-autrui (Bukowski et al, 2020). Certains domaines explorant les biais de traitement et leur possible lien avec le Soi, par exemple à l’œuvre dans l’anxiété, le jeu pathologique ou la consommation d’alcool (e.g., De Greck et al, 2009), pourraient aussi s’en emparer dans de futures recherches.…”
Section: Perspectives De Rechercheunclassified
“…Stimuli (shapes) associated with social labels (SELF, FRIEND, STRANGER) have been observed to induce a self-bias effect where participants exhibited faster reaction time and better accuracy to selfassociated stimuli . Previously associated stimuli, when presented as the operant stimulus, influenced intentional binding through retrospective inference (Makwana & Srinivasan, 2019).…”
Section: Introductionmentioning
confidence: 99%